Telephone‐assisted self‐help for parents of children with attention‐deficit/hyperactivity disorder who have residual functional impairment despite methylphenidate treatment: a randomized controlled trial. (23rd November 2016) - Dose, Christina; Hautmann, Christopher; Buerger, Mareike; Schuermann, Stephanie; Woitecki, Katrin; Doepfner, Manfred
Abstract : Background: Self‐help parenting interventions have been shown to be effective in the management of children with attention‐deficit/hyperactivity disorder (ADHD) and may be useful when there are barriers to face‐to‐face therapist‐led parent trainings. Previous studies indicate that behavioral interventions might be a useful adjunct to medication in children with residual ADHD symptoms, and regarding comorbid oppositional symptoms and multiple domains of functional impairment. In the present study, we examined whether a telephone‐assisted self‐help (TASH) parenting behavioral intervention (written materials plus telephone counseling) enhanced the effects of methylphenidate treatment in children with ADHD. Methods: In this randomized controlled trial, parents of 103 school‐aged children with ADHD and residual functional impairment despite methylphenidate treatment were randomly assigned to either the enhancement group, which received the TASH intervention as adjunct to routine clinical care (including continued medication), or to the active control group, which received routine clinical care only (including continued medication). Parent‐completed outcome measures at baseline and at 12 months (postassessment) included functional impairment, ADHD symptoms, oppositional defiant disorder (ODD) symptoms, parenting behavior, and parental satisfaction with the intervention (ClinicalTrials.gov: NCT01660425; URL:https://clinicaltrials.gov/ct2/show/NCT01660425 ). Results: Intention‐to‐treat analyses of covariance (ANCOVAs), which controlled for baseline data, revealed significant and moderate intervention effects for ODD symptoms and negative parenting behavior at the postassessment, whereas per‐protocol analyses additionally showed significant and moderate effects on functional impairment (primary outcome). Parents expressed high satisfaction with the program. Conclusions: The TASH program enhances effects of methylphenidate treatment in families who complete the intervention. The discontinuation rate of about 30% and comparison between completing and discontinuing families suggest that the program may be more suitable for families with a higher educational level and fewer additional stresses.